Iran-India Scientific Interactions in the Field of Medicine during the Abbasid Caliphate: The Role of Gundishapur in Transmitting Indian Medical Heritage to the Islamic World - Mohammad Hashemimehr; Farah Ahad (CV. FOUNDAE, 2026)
India is recognized as one of the earliest centers for the formation and flourishing of medical knowledge in the ancient world. This study, employing a library-based approach with a descriptive-analytical methodology, investigates the scientific interactions between Iran and India, with a specific emphasis on the role of Gundishapur in transmitting Indian medical heritage to the Islamic world. The findings indicate that Indian medical knowledge, particularly from the Sasanid era, entered the scientific sphere of Iran via Gundishapur. Here, it either integrated with or influenced existing medical schools. Indian physicians possessed significant expertise and experience in areas such as psychological medicine, acupuncture, and herbal medicine. This knowledge, through connections with Gundishapur, subsequently influenced medicine during the Islamic period. Furthermore, with the expansion of Islam and the conquest of India, certain Indian medical ideas and teachings found their way into the courts of the Abbasid Caliphs, and a number of Indian physicians served as medical advisors to the Caliphs. In light of the Translation Movement and the Abbasids’ attention to medical sciences, several Sanskrit and Pahlavi texts were translated into Arabic. Consequently, Gundishapur served as a crucial intermediary, facilitating the transmission and development of a segment of Indian medical knowledge within Islamic civilization.